FOXO1 Is Present in Stomach Epithelium and Determines Gastric Cell Distribution - Wendy M. McKimpson; Taiyi Kuo; Takumi Kitamoto; Sei Higuchi; Jason C. Mills; Rebecca A. Haeusler; Domenico Accili (Gastro Hep Advances, 2022)
Background and Aims: Stomach cells can be converted to insulin-producing cells by Neurog3, MafA, and Pdx1 overexpression. Enteroendocrine cells can be similarly made to produce insulin by the deletion of FOXO1. Characteristics and functional properties of FOXO1-expressing stomach cells are not known. Methods: Using mice bearing a FOXO1-GFP knock-in allele and primary cell cultures, we examined the identity of FOXO1-expressing stomach cells and analyzed their features through loss-of-function studies with red-to-green fluorescent reporters. Results: FOXO1 localizes to a subset of Neurog3 and parietal cells. FOXO1 deletion ex vivo or in vivo using Neurog3-cre or Atp4b-cre increased numbers of parietal cells, generated insulin- and C-peptide-immunoreactive cells, and raised Neurog3 messenger RNA. Gene expression and ChIP-seq experiments identified the cell cycle regulator cyclin E1 (CCNE1) as a FOXO1 target. Conclusion: FOXO1 is expressed in a subset of stomach cells. Its ablation increases parietal cells and yields insulin-immunoreactive cells, consistent with a role in lineage determination.